Internal Determinants of Tax Planning: The Mediating Role of Transfer Pricing in Industrial Firms - Molkend Siringoringo; Daulat Freddy (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This study investigates the effect of financial performance, leverage, and firm size on tax planning, with transfer pricing as a mediating variable. Grounded in Agency Theory and Positive Accounting Theory, this research explains how firm characteristics influence tax planning strategies. The sample consists of manufacturing firms listed on the Indonesia Stock Exchange. Tax planning is proxied by the Effective Tax Rate (ETR), financial performance by Return on Equity (ROE), leverage by Debt to Equity Ratio (DER), firm size by the natural logarithm of total assets, and transfer pricing by related-party receivables. The results show that financial performance and leverage significantly affect tax planning, while firm size does not consistently influence tax planning. Transfer pricing is proven to mediate the relationship between financial performance and tax planning, as well as between leverage and tax planning. However, it does not mediate the relationship between firm size and tax planning. These findings indicate that profitable and highly leveraged firms tend to use transfer pricing as a strategic tool for tax optimization, whereas larger firms are more cautious due to regulatory pressure. This study contributes to the literature on corporate tax behavior and provides practical implications for regulators and firms in designing effective and compliant tax strategies.